THE CHARACTERISTIC OF CORRIDOR STREET SPACE CASE STUDY: THE CORRIDOR OF JALAN VETERAN PENGGAL KLENTENG – JALAN SIMPANG ULIN - Irwan Yudha Hadinata (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2017)
The street space is a part of urban public spaces. The various functions of street space in generally are as a mode of transporting space, as shared space for citizens and also as an architectural expression of spaces that contain the collective memory of its citizens. This research is focusing on the uniqueness of the street networks and canals in the city of Banjarmasin. Further, exploration of the combination of streets and canals is done to get the spatial characteristics. The purpose of this research is to determine how and why the street spaces changed and what components have influenced the characteristics of the space in the city of Banjarmasin. This research uses an empirism paradigm with the case study method focusing on the corridor of Jalan Veteran. The analytical method used is to discover street spaces in both two (2) and three (3) dimensional perspectives. Simplification and categorization patterns conducted to reveal the main characteristics of the street spaces. The findings of the study show that the formal and informal characters of each street space influence the growth rate of the buildings, the changing face of the region, and the shift of the old buildings into the new ones. Double canals are known as formal characteristic and single canals are known as informal ones. The chanal elements in the street spaces have a big influence to change the street spaces' characteristic. Keywords: characteristic, street space, space transformation, canal